2014
DOI: 10.3791/51171
|View full text |Cite|
|
Sign up to set email alerts
|

Initiation of Metastatic Breast Carcinoma by Targeting of the Ductal Epithelium with Adenovirus-Cre: A Novel Transgenic Mouse Model of Breast Cancer

Abstract: Breast cancer is a heterogeneous disease involving complex cellular interactions between the developing tumor and immune system, eventually resulting in exponential tumor growth and metastasis to distal tissues and the collapse of anti-tumor immunity. Many useful animal models exist to study breast cancer, but none completely recapitulate the disease progression that occurs in humans. In order to gain a better understanding of the cellular interactions that result in the formation of latent metastasis and decr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
20
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 21 publications
(22 citation statements)
references
References 35 publications
2
20
0
Order By: Relevance
“…By using high-titer lentiviral vector preparations, we achieved extensive transduction of the ductal system and in vivo Cre-mediated recombination when using Lenti-Cre preparations in mT/mG Cre reporter mice. This recapitulates previous studies using adenoviral vectors for somatic Cre delivery to murine mammary tissue (Rutkowski et al 2014;Tao et al 2014). We observed that the target cell population was composed of both CK8-positive luminal epithelial cells and CK14-positive basal cells.…”
Section: Discussionsupporting
confidence: 90%
See 2 more Smart Citations
“…By using high-titer lentiviral vector preparations, we achieved extensive transduction of the ductal system and in vivo Cre-mediated recombination when using Lenti-Cre preparations in mT/mG Cre reporter mice. This recapitulates previous studies using adenoviral vectors for somatic Cre delivery to murine mammary tissue (Rutkowski et al 2014;Tao et al 2014). We observed that the target cell population was composed of both CK8-positive luminal epithelial cells and CK14-positive basal cells.…”
Section: Discussionsupporting
confidence: 90%
“…S1C,D). These data demonstrate that intraductal injection of Cre-encoding lentiviruses induces efficient in vivo recombination of conditional alleles in mammary epithelium, as previously shown by other groups using Adeno-Cre (Russell et al 2003;Rutkowski et al 2014;Tao et al 2014).…”
Section: Transduction Of Ductal Epithelial Cells By Intraductal Injecsupporting
confidence: 86%
See 1 more Smart Citation
“…To investigate the therapeutic potential of combining trametinib and ALT-803 against established KRas -mutated tumors, we utilized a syngeneic tumor model derived from an autochthonous breast cancer initiated in triple transgenic (L-Stop-L- KRas G12D p53 flx/flx L-Stop-L- Myristoylated p110α ) mice with adenovirus-Cre (11, 12, 33). We chose this cell line, termed br east- p 53- K Ras- p110 alpha (Brpkp110), to model treatment against tumors that evade single molecule targeting of the MAPK pathway through PI3K activation, as has been commonly reported in human cancer cells (3436).…”
Section: Resultsmentioning
confidence: 99%
“…The Brpkp110 primary mammary tumor cell line was generated by culturing a mechanically dissociated C57BL/6 L-Stop-L- Kras G12D p53 flx/flx L-Stop-L- Myristoylated p110α − GFP flx/+ primary breast tumor mass as previously described (15). Tumor cells were passaged a total of 10 times and tested for mycoplasma before deriving the Brpkp110 cell line.…”
Section: Methodsmentioning
confidence: 99%